The Role of Hemoglobin Subunit Delta in the Immunopathy of Multiple Sclerosis: Mitochondria Matters - Derakhshani, Afshin; Safarpour, Hossein; Abdoli Shadbad, Mahdi; Hemmat, Nima; Leone, Patrizia; Asadzadeh, Zahra; Pashazadeh, Mehrdad; Baradaran, Behzad; Racanelli, Vito (Frontiers in Immunology, 2021)
Background: Although the exact pathophysiology of MS has not been identified, mitochondrial stress can be one of the culprits in MS development. Herein, we have applied microarray analysis, single-cell sequencing analysis, and ex vivo study to elucidate the role of mitochondrial stress in PBMCs of MS patients. Methods: For this purpose, we analyzed the GSE21942 and GSE138266 datasets to identify the DEGs and hub genes in the PMBCs of MS patients and describe the expression of shared genes in the different immune cells. The GO pathway analysis of DEGs and turquoise module genes were conducted to shed light on their biological significance. To validate the obtained results, the gene expression of HBD, as the most remarkable DEG in the PMBCs of affected patients, was measured in the PMBCs of healthy donors, treatment-naïve MS patients, and MS patients treated with GA, fingolimod, DMF, and IFNβ-1α. Results: Based on WGCNA and DEGs analysis, HBD, HBM, SLC4A1, LILRA5, SLC25A37, SELENBP1, ALYREF, SNRNP40, and HINT3 are the identified common genes in the PMBCs. Using single-cell sequencing analysis on PBMCs, we have characterized various cell populations in MS and illustrated the common gene expression on the different immune cells. Furthermore, GO pathway analysis of DEGs, and turquoise module genes have indicated that these genes are involved in immune responses, myeloid cell activation, leukocyte activation, oxygen carrier activity, and replication fork processing bicarbonate transport pathways. Our ex vivo investigation has shown that HBD expression in the treatment-naïve RRMS patients is significantly increased compared to healthy donors. Of interest, immunomodulatory therapies with fingolimod, DMF, and IFNβ-1α have significantly decreased HBD expression. Conclusion: HBD is one of the remarkably up-regulated genes in the PMBCs of MS patients. HBD is substantially up-regulated in treatment-naïve MS patients, and immunomodulatory therapies with fingolimod, DMF, and IFNβ-1α can remarkably down-regulate HBD expression. Based on the currently available evidence, the cytoprotective nature of HBD against oxidative stress can be the underlying reason for HBD up-regulation in MS. Nevertheless, further investigations are needed to shed light on the molecular mechanisms of HBD in the oxidative stress of MS patients.